Screening Deep Eutectic Solvents for CO2 Capture With COSMO-RS - Liu, Yanrong; Yu, Hang; Sun, Yunhao; Zeng, Shaojuan; Zhang, Xiangping; Nie, Yi; Zhang, Suojiang; Ji, Xiaoyan (Frontiers in Chemistry, 2020)
In this work, 502 experimental data for CO2 solubilities and 132 for Henry’s constants of CO2 in DESs were comprehensively summarized from literatures and used for further verification and development of COSMO-RS. Large systematic deviations of 62.2, 59.6, 63.0 and 59.1% for the logarithmic CO2 solubilities in the DESs (1:2, 1:3, 1:4, 1:5), respectively, were observed for the prediction with the original COSMO-RS, while the predicted Henry’s constants of CO2 in the DESs (1:1.5, 1:2, 1:3, 1:4, 1:5) at temperatures ranging of 293.15-333.15 K are more accurate than the predicted CO2 solubility with the original COSMO-RS. To improve the performance of COSMO-RS, 502 data points of CO2 solubility in the DESs (1:2, 1:3, 1:4, 1:5) were used for correcting COSMO-RS with a temperature-pressure dependent parameter, and the CO2 solubility in the DES (1:6) was predicted to further verify the performance of the corrected model. The results indicate that the corrected COSMO-RS can significantly improve the model performance with the ARDs decreasing down to 6.5, 4.8, 6.5 and 4.5% for the DESs (1:2, 1:3, 1:4 and 1:5), respectively, and the corrected COSMO-RS with the universal parameters can be used to predict the CO2 solubility in DESs with different mole ratios, for example, for the DES (1:6), the corrected COSMO-RS significantly improves the prediction with an ARD of 10.3% that is much lower than 78.2% provided by the original COSMO-RS. Additionally, the result from COSMO-RS shows that the σ-profiles can reflect the strength of molecular interactions between an HBA (or HBD) and CO2, determining the CO2 solubility, and the dominant interactions for CO2 capture in DESs are the H-bond and Van der Waals force, followed by the misfit based on the analysis of the predicted excess enthalpies.